The role of credit rating of the ESG debt instruments issuers - Frydrych, Sylwia (Economics and Environment, 2023)
The aim of this article is to assess whether having a creditworthiness assessment from more than one credit rating agency by issuers of ESG debt instruments affects the number of issues and the average amount issued. The empirical research was carried out using the observation method and the analysis of source documents. In the analysed period, 53.38% of issuers received ratings at least from one CRAs as S&P, Moody’s, and Fitch. The results of the conducted research indicate that the number of ESG debt instruments and the average issue amount were affected by the number of ratings given to the issuer. A database collected from Refinitiv Eikon for the period between 2012 and 2021 allows us to conclude that it is enough to have two credit ratings. The conclusions of this study can be used in the process of obtaining financing for ESG projects.